ANALYSIS OF BUMDESA COMPETITIVENESS STRATEGY THROUGH THE UTILIZATION OF TOURISM OBJECTS TO IMPROVE COMMUNITY WELFARE - Kurhayadi Kurhayadi; Muhammad Yusuf; Sri Masrifah; Erinda Destry Rincani; Muhammad Fauzi (Badan Penerbit STIEPARI Press, 2022)
The purpose of this study is to formulate an analysis of the competitiveness strategy of village-owned enterprises through the use of tourist objects. This study uses a qualitative approach through in-depth interviews with several informants. The informants used in this study were 15 informants, consisting of village heads, BUMDesa managers, community leaders, and visitors. The analytical method used to formulate an analysis of BUMDesa's competitiveness strategy is SWOT analysis (Strength, Weakness, Opportunity, and Threat). Before carrying out this analysis stage, a data quality test is first carried out, namely a validity test and a reliability test.